Generalized iterative procedures and their applications to Banach space valued functions in abstract fractional calculus - Anastassiou, George A.; Argyros, Ioannis K. (SeMA journal, 2018)
The objective in this study is to use generalized iterative procedures in order to approximate solutions of an equation on a Banach space setting. In particular, we present a semi-local convergence analysis for these methods. Some applications are suggested including Banach space valued functions of fractional calculus, where all integrals are of Bochner-type.